PERAN KOMITE SEKOLAH DALAM PEMBERDAYAAN MASYARAKAT DI KOTA BANJARMASIN - Muhammad Insanul Kamil (Al-Manba, 2025)
This study aims to analyze the role of school committees in community empowerment in Banjarmasin City. School committees are independent bodies established to facilitate community involvement in improving the quality of education services. In the context of community empowerment, school committees act as strategic partners in decision-making, supervision, and support for the implementation of education in schools. This research employs a qualitative approach with data collected through interviews, observations, and documentation. The findings indicate that school committees in several schools in Banjarmasin have made positive contributions in encouraging community participation, particularly in the form of moral, material, and idea-based support for educational programs. However, their role still faces several challenges, such as limited understanding of their duties and functions, as well as inadequate human resource capacity. Therefore, strengthening the capacity and role of school committees through training, outreach, and supportive regulations is necessary to optimize their contribution to community empowerment